The Mapping of Organizational Culture to Find Determinant Factors for Behavioral Intention to USe in IT Utilization Among Credit Unions in Indonesia - Indra, Samsie; T.K.A, Rahman; Suarga, . (2020)
—Measurement of IT acceptance at the organizational level is no more sufficient if only based on individual acceptance factors. There is an attempt to measure IT acceptance in organizations by considering organizational culture as a determinant factor. Competitive Value Framework is used to determine the position of the credit union organizations. This study used an organizational culture which derived from the Organizational Culture Assessment Instrument (OCAI) and used the value that influences the chosen quadrant as a determinant factor for behavioral intention to use IT. The result showed that Credit Union (CU) in Saluampak placed in Hierarchy quadrant. This result identified four factors: timelines, efficiency, uniformity, and consistency as a value that will use as a determinant of behavioral intention to use IT in CU. The most significant point is that this mapping creates cultural, organizational principles extracted from the hierarchical quadrant and is used as a determinant of conduct purpose to use IT in a CU context.